Analysis of the Decision to Purchase Motorcycle Towing Services - Taruwara, Apta Tantra; Wijayanti, Risna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The increase in motorcycle towing business in Indonesia, particularly in Malang City, is the reason for this research to be conducted. Its objective is to identify the internal and external aspects for people’s decision of use the towing service in Malang City. The sample of this qualitative descriptive research was selected using purposive sampling technique, resulting in the inclusion of eight informants. The data was harvested via interviews and documentation. This study finds that the internal aspects that drive people’s decision to purchase the motorcycle towing service are consumer’s need for the service, the quality of the service, and the cost for having the service. Meanwhile, the external aspects are lifestyle, culture, motivation and involvement. Based on the identified aspects, it can be concluded that service quality is the most important factor. High service quality can produce satisfaction for customers and make them to repurchase the service. Another crucial factor for the purchase decision is marketing network. Broad marketing network can enhance company visibility and improve people’s awareness of the offered service. Tantra Storing Malang needs to conduct its own research in order to identify other factors that can also influence the decision to purchase motorcycle towing service in Malang City, by which the company can have a better understanding about customer needs and develop more effective marketing strategies.